2013
DOI: 10.4103/1119-3077.113446
|View full text |Cite
|
Sign up to set email alerts
|

The value of international prostate symptom scoring system in the management of BPH in Jos, Nigeria

Abstract: The study has shown that IPSS is a valuable tool in management of patients with BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The linear increase in the prevalence of the symptoms with age is consistent with the earlier report and other reports on the prevalence of BPH. This is understandable since BPH is known to be age-related (Seim et al, 2005;Chokkalingam et al, 2012;Amu et al, 2013;Parsons et al, 2013). Chokkalingam et al (2012) reported a prevalence of 19.9% for moderate-to-severe symptoms of BPH in Ghana and concluded that "BPH and/or LUTS appear to be quite common among older Ghanaian men".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear increase in the prevalence of the symptoms with age is consistent with the earlier report and other reports on the prevalence of BPH. This is understandable since BPH is known to be age-related (Seim et al, 2005;Chokkalingam et al, 2012;Amu et al, 2013;Parsons et al, 2013). Chokkalingam et al (2012) reported a prevalence of 19.9% for moderate-to-severe symptoms of BPH in Ghana and concluded that "BPH and/or LUTS appear to be quite common among older Ghanaian men".…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that it is valid for use in Nigeria for both diagnosis and management of BPH (Ezeanyika et al, 2006;Amu et al, 2013) and was therefore, used in this study to diagnose the clinical symptoms of BPH. Mild, moderate and severe symptoms of BPH were defined by a symptom score of 0-7, 8-19 and 20-35 points, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Benign prostatic hyperplasia (BPH), urethra stricture and carcinoma of the prostate (CaP) are the primary causes of bladder outlet obstruction. 2,3 Of them BPH is the most common etiological factor of bladder outlet obstruction in men older than 50 years of age. In the present study, the male preponderance (94%) was observed with the high incidence of BPH (53%).…”
Section: Discussionmentioning
confidence: 99%
“…The condition is common in older men. 2 Most common cause of bladder outlet obstruction in men is benign prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 99%